Strokovne podlage sistema za ocenjevanje kakovosti izvedbe del izvajalcev gozdarskih storitev - Stare, Darja (Acta silvae et ligni, 2026)
Sustainable, close-to-nature, and multifunctional forest management requires not only appropriate planning but also high-quality implementation and systematic monitoring of forest operations. Structural changes in the forestry sector, particularly the increase in the number of smaller forest service providers, have heightened the need for objective and comparable approaches to assessing the quality of forest operations. This paper presents the development of a foundation for the systematic assessment of the quality of work performed by forestry contractors in Slovenia. Based on a review of legislative and professional frameworks, a set of criteria and measurable indicators was developed, structured by work phases (felling, harvesting, silvicultural and protection works, transport). The criteria were evaluated by an expert group using the SMART multi-criteria method. The final proposal includes 13 criteria and 37 indicators, enabling standardised, transparent, and repeatable quality assessment. The paper highlights the importance of distinguishing between formal compliance and the actual quality of work implementation and contributes to the discussion on sustainable forest management and the development of digital support tools for assessment.
Keywords: criteria; evaluation; forestry; forestry contractors; gozdarske storitve; gozdarstvo; indicators; indikatorji; izvajalci; merila; ocenjevanje; sustainable; trajnost